Effect of silane integrated sol–gel derived in situ silica on the properties of nitrile rubber. Issue 15 (18th February 2014) - Kapgate, Bharat P.; Das, Chayan; Basu, Debdipta; Das, Amit; Heinrich, Gert; Reuter, Uta
ABSTRACT Nitrile rubber/silica composites are prepared by a sol–gel process using tetraethoxysilane as precursor in the presence of γ‐mercaptopropyltrimethoxysilane as a silane coupling agent. Here, we follow a novel processing route where the silica particles are generated inside the rubber matrix before compounding with vulcanizing ingredients. The effect of in situ generated silanized silica on the properties of the rubber composite has been evaluated by studying curing characteristics, morphology, mechanical and dynamic mechanical properties. Enhanced rubber–filler interaction of these composites is revealed from stress–strain studies and dynamic mechanical analysis. Excessive use of silane shows an adverse effect on mechanical properties of the composites. Due to finer dispersed state of the in situ silica and enhanced rubber–filler interaction, the mechanical properties and thermal stability of the composites are improved compared to corresponding ex situ processed composite. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40054.